2012
DOI: 10.1161/circulationaha.111.061986
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Hematopoiesis Generates Ly-6C high Monocytes That Infiltrate Atherosclerotic Lesions

Abstract: Background Atherosclerotic lesions are believed to grow via the recruitment of bone marrow-derived monocytes. Among the known murine monocyte subsets, Ly-6Chigh monocytes are inflammatory, accumulate in lesions preferentially, and differentiate. Here we hypothesized that the bone marrow outsources the production of Ly-6Chigh monocytes during atherosclerosis. Methods and Results Using murine models of atherosclerosis and fate-mapping approaches, we show that hematopoietic stem and progenitor cells (HSPC) prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
423
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(447 citation statements)
references
References 46 publications
23
423
1
Order By: Relevance
“…While monocytes are also formed in the liver and spleen [70][71][72], the view that monocytes are derived from the bone marrow has been established since the early 1960s and still dominates [73]. The monocytes produced from the bone marrow exit to the circulatory system in a C-C chemokine receptor 2 (CCR2)-dependent manner and enter tissues to give rise to tissue macrophages [74].…”
Section: Monocytes and Monocyte-derived Macrophagesmentioning
confidence: 99%
“…While monocytes are also formed in the liver and spleen [70][71][72], the view that monocytes are derived from the bone marrow has been established since the early 1960s and still dominates [73]. The monocytes produced from the bone marrow exit to the circulatory system in a C-C chemokine receptor 2 (CCR2)-dependent manner and enter tissues to give rise to tissue macrophages [74].…”
Section: Monocytes and Monocyte-derived Macrophagesmentioning
confidence: 99%
“…Still, monocytes are also produced by extra-medullary hematopoiesis in the spleen and increase under inflammatory conditions such as atherosclerosis and cancer as recently shown [9,10]. In the bone marrow, monocytes are generated from HSC in a sequential process of differentiation and commitment steps [3,11], collectively called monopoiesis (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…6) Immediately after MI, monocytes in the splenic reservoir are mobilized to the infarcted myocardium via activation of the angiotensin II type 1 receptor 7) and then, bone marrow-derived monocytes accumulate by MCP1-CCR2-mediated mechanisms. 8,9) Monocytes accumulating in the infarcted heart consist of at least two phases: accumulation of Ly-6C high(hi) inflammatory monocytes (CD14 ++ CD16 -monocytes in humans) immediately after MI and Ly-6C low(lo) reparative monocytes (CD14 + CD16 ++ monocytes in humans) in the later phase. 10) In humans, it was recently reported that the CD14 ++ CD16 + "intermediate" subset of monocytes is also associated with LV remodeling after AMI in diabetic patients.…”
Section: Editorial P472mentioning
confidence: 99%